The Implementing Tad (Transition - Action - Details) Teaching Strategy On Students’ Writing Ability At First Grade Of Sma Pgri Pekanbaru - Eggi Pratama; Mukhayar Mukhayar; Refnaldi Refnaldi (Postgraduate School, Universitas Negeri Padang, 2020)
The aim of this study is to find out the effect of TAD teaching strategy on students’ writing ability at first grade of SMA PGRI Pekanbaru. The design of the research is quasi experimental research with factorial design 2x2. The samples were X IPS 1 as experimental class and X IPS 3 as control class. The samples were selected by using cluster random sampling. The instruments were writing test of recount text. These instruments were tried out first to another class which had similar capabilities to both experiment and control class. The data were analyzed by using T-test. The result of this research shows that TAD teaching strategy produces higher result on students’ writing ability of recount text compared to Small Group Discussion.